2017
DOI: 10.1186/s12967-017-1210-z
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of platelet releasate products for clinical applications in cell therapy: a mathematical approach

Abstract: BackgroundStandardized animal-free components are required for manufacturing cell-based medicinal products. Human platelet concentrates are sources of growth factors for cell expansion but such products are characterized by undesired variability. Pooling together single-donor products improves consistency, but the minimal pool sample size was never determined.MethodsSupernatant rich in growth factors (SRGF) derived from n = 44 single-donor platelet-apheresis was obtained by CaCl2 addition. n = 10 growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Different approaches such as (nano)filtration and ultraviolet irradiation are commonly used for pathogen inactivation (Tekkatte et al, 2011). Human blood derivatives also present high batch-to-batch variability, and pooling large numbers of individual samples is necessary (Agostini et al, 2017). Components most commonly employed in XF cell culture are platelet derivatives and serum/plasma derivatives (Table 2; Burnouf, Strunk, Koh, & Schallmoser, 2016;Karnieli et al, 2017;Tekkatte et al, 2011).…”
Section: Human Blood-derived Components Used In Xf Ec Culturementioning
confidence: 99%
“…Different approaches such as (nano)filtration and ultraviolet irradiation are commonly used for pathogen inactivation (Tekkatte et al, 2011). Human blood derivatives also present high batch-to-batch variability, and pooling large numbers of individual samples is necessary (Agostini et al, 2017). Components most commonly employed in XF cell culture are platelet derivatives and serum/plasma derivatives (Table 2; Burnouf, Strunk, Koh, & Schallmoser, 2016;Karnieli et al, 2017;Tekkatte et al, 2011).…”
Section: Human Blood-derived Components Used In Xf Ec Culturementioning
confidence: 99%
“…Interindividual differences between platelet donors and medium additive manufacturing methods [ 10 ] can strongly affect the capability to stimulate cell growth in vitro . Especially when dealing with small scale manufactured medium additives for academic purposes, quality controls are needed to assess the capacity of the ancillary product to stimulate cell proliferation in vitro [ 9 ]. In this paper we aimed to define a rapid and cost effective test to potentially predict the impact of a medium additive on cell growth rate: this represents a significant achievement, improving both production and quality control processes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, results obtained by the luminescence based cell proliferation assay demonstrated that medium additives A (recalcified PRP) and B (recalcified PPP) induced a faster ASC growth rate, when compared to additives obtained by freeze and thaw approach. Considering the manufacturing process, medium additive A is extremely close to the product we previously named SRGF [ 2 , 9 ]. SRGF used in this work was obtained from different aliquots of human PRP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations